2018
DOI: 10.1177/1687814018795961
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evolution and migration behavior of silver thin films on flexible substrates during thermal cycle testing

Abstract: To understand morphological evolution and migration behavior caused by stress migration and thermal fatigue of silver thin films on flexible substrates, bending tests were conducted with different bending angles for two types of thermal tests. Furthermore, the effect of stress migration and thermal fatigue on the electrical conductivity of the silver thin films was discussed. The experimental samples were silver thin films printed on flexible paper for these tests. In an ultra-low cycle thermal test, the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In metallic wires, the wind force causes preliminary damage (voids) on the cathode side and hillocks on the anode side, whereas the direct force produces void on the anode side and hillocks on the cathode side [99]. Quan Sun and his team [100] studied the effect of stress migration and thermal fatigue of silver thin films on the flexible substrate. Their results indicated that the combination of thermal fatigue and stress migration increases the number of atomic diffusions then causes the thin films to experience cracks, voids, and hillocks, which could cause the electrical conductivity to deteriorate [100].…”
Section: Characteristics Of Emmentioning
confidence: 99%
See 1 more Smart Citation
“…In metallic wires, the wind force causes preliminary damage (voids) on the cathode side and hillocks on the anode side, whereas the direct force produces void on the anode side and hillocks on the cathode side [99]. Quan Sun and his team [100] studied the effect of stress migration and thermal fatigue of silver thin films on the flexible substrate. Their results indicated that the combination of thermal fatigue and stress migration increases the number of atomic diffusions then causes the thin films to experience cracks, voids, and hillocks, which could cause the electrical conductivity to deteriorate [100].…”
Section: Characteristics Of Emmentioning
confidence: 99%
“…Quan Sun and his team [100] studied the effect of stress migration and thermal fatigue of silver thin films on the flexible substrate. Their results indicated that the combination of thermal fatigue and stress migration increases the number of atomic diffusions then causes the thin films to experience cracks, voids, and hillocks, which could cause the electrical conductivity to deteriorate [100]. According to Liu et al [101], copper diffuses into the silver layer's vacancies after the annealing process, and then the vacancies transfer to the copper layer.…”
Section: Characteristics Of Emmentioning
confidence: 99%